Effects of business school student's study time on the learning process. Issue 2 (7th November 2016) - Tetteh, Godson Ayertei
Abstract : Purpose: This paper aims to clarify the relationship between the student's study time and the learning process in the higher education system by adapting the total quality management (TQM) principles-process approach. Contrary to Deming's (1982) constancy of purpose to improve the learning process, some students in higher education postpone their studies till the last few weeks of an examination. Design/methodology/approach: The paper opted for an experimental study with three different classes of business school students. The experimental research question was "Do student's study time (massed or distributed spacing) has an impact on the learning process?" Findings: Results indicated that students in the "Strictly supervised study time" group improved on their learning process more than the "Not Strictly Supervised study time" and the control group. It is important for students to manage their own learning activities and follow a regular study time and constantly improve their learning process as proposed by Deming (1982). Research limitations/implications: This study used restricted to undergraduate business school students in a university in Ghana, and may not necessarily be applicable universally. One other limitation was that the authors did not control for lecturer's expectancies and how these may have influenced the students' learning process. Another potential limitation was that TQM was the only subject area used for this study. Practical implications: This objective of the study is to use the TQM principles of process approach, the Learning Theory and the Learning Strategies from the Motivated Strategies for Learning Questionnaire (MSLQ) – Pintrich et al. (1991) – to support theoretical and practical implications of the relationship between the student's study time and the learning process. The results imply that students must take a more active role in their learning by having a regular study time. Originality/value: Currently, to the best of the authors' knowledge, there are not many experiment-based studies on a student's study time using the MSLQ-Pintrich et al. (1991) approach. This study contributes to the literature by examining how a student's study time (massed or distributed spacing) has an impact on the learning process.